2017
DOI: 10.1175/mwr-d-15-0451.1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Evolving Microphysical and Kinematic Structure of Northeastern U.S. Winter Storms from Dual-Polarization Doppler Radar

Abstract: The recent Weather Surveillance Radar-1988 Doppler (WSR-88D) network upgrade to dual-polarization capabilities allows for bulk characterization of microphysical processes in northeastern U.S. winter storms for the first time. In this study, the quasi-vertical profile (QVP) technique (wherein data from a given elevation angle scan are azimuthally averaged and the range coordinate is converted to height) is extended and applied to polarimetric WSR-88D observations of six Northeast winter storms to survey their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 64 publications
4
42
0
Order By: Relevance
“…The signature of needle and/or columnar crystals in a temperature range from À8 to À3°C, where ice particles seeded in the MPL and secondary ice formation via the Hallett-Mossop ice multiplication mechanism (Hallett & Mossop, 1974) could be active, is often observed in Arctic mixed-phase clouds in linear depolarization ratio measurements . Similar signatures were observed in midlatitude winter storms and convective systems (e.g., Giangrande, Toto, Bansemer, et al, 2016;Kumjian et al, 2016;Kumjian & Lombardo, 2017;Sinclair et al, 2016;Zawadzki et al, 2001). Kumjian et al (2016) observed K DP enhancements produced by needle and columnar crystals in secondary ice formation regions.…”
Section: Mixed-phase Layersupporting
confidence: 66%
See 1 more Smart Citation
“…The signature of needle and/or columnar crystals in a temperature range from À8 to À3°C, where ice particles seeded in the MPL and secondary ice formation via the Hallett-Mossop ice multiplication mechanism (Hallett & Mossop, 1974) could be active, is often observed in Arctic mixed-phase clouds in linear depolarization ratio measurements . Similar signatures were observed in midlatitude winter storms and convective systems (e.g., Giangrande, Toto, Bansemer, et al, 2016;Kumjian et al, 2016;Kumjian & Lombardo, 2017;Sinclair et al, 2016;Zawadzki et al, 2001). Kumjian et al (2016) observed K DP enhancements produced by needle and columnar crystals in secondary ice formation regions.…”
Section: Mixed-phase Layersupporting
confidence: 66%
“…Schrom et al (2015) suggested a polarimetric technique to separate contributions from aggregates and dendrites in the DGL of midlatitude winter storms. Polarimetric signatures of the secondary ice mixed with aggregated and rimed snow in layers with temperature around À5°C were found by cloud and precipitation radar measurements in high-latitude deeper snow clouds Sinclair et al, 2016), midlatitude mesoscale convective systems Kumjian et al, 2016), and midlatitude snowstorms (Kumjian & Lombardo, 2017). However, combining polarimetric measurements with the analysis of Doppler spectra yields a much better chance to identify and separate different types of ice, and to quantify their amounts if their corresponding fall velocities are associated with separate peaks in the Doppler spectrum.…”
Section: Introductionmentioning
confidence: 97%
“…As noted earlier in section , ETCs are of importance to the U.S. East Coast. A substantial body of work has examined aspects of East Coast winter storms, which have major societal impacts ranging from commerce to public safety over the mid‐Atlantic and northeastern United States (e.g., Brennan & Lackmann, ; Charles & Colle, , ; Evans & Jurewicz, ; Ganetis & Colle, ; Hirsch et al, ; Kocin & Uccellini, ; Kumjian & Lombardo, ; Nicosia & Grumm, ; Novak et al, ; Novak & Colle, ; Root et al, ; Sanders & Bosart, ; Zhang et al, ). In fact, the oldest study identified in this review paper is related to cyclogenesis over the East Coast, which is relevant to the modeling and forecasting of such storms (Miller, ).…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Dual‐polarization radar has been instrumental in improving quantitative rainfall estimation (e.g., Cifelli et al, ; Giangrande & Ryzhkov, ; Ryzhkov et al, ), hydrometeor classification (Dolan & Rutledge, ; Chandrasekar et al, ; Park et al, ; Ryzhkov et al, ; Vivekanandan et al, ), microphysical fingerprinting (Kumjian & Prat, ; Kumjian & Ryzhkov, , ; Schrom & Kumjian, ), and advancing our understanding of organized precipitation systems including supercells (e.g., Kumjian & Ryzhkov, ; Snyder et al, ), mesoscale convective systems (e.g., Zrnić et al, ), and winter storms (e.g., Griffin et al, ; Kumjian & Lombardo, ). All of these studies have focused on storm systems that occur predominantly over land.…”
Section: Introductionmentioning
confidence: 99%